Raiding the gene pool : the social construction of mixed race / Jill Olumide. - Olumide, Jill. (Pluto Press, 2002)
"High profile 'mixed race' stars like Tiger Woods have brought the politics of identity into the mainstream. Jill Olumide argues that we must examine the contradictions inherent in the term 'mixed race' in order to reach a fuller understanding of the variety in human experience and identity." "Olumide demonstates that there are distinctive features of mixed race experience that span time and place. By comparing contemporary experiences of mixed race, collected through a series of interviews and workshops, with those of past populations in different parts of the world, she explains how its meaning alters with national boundary, historical context, class, gender and ethnicity. Showing how different communities are linked by social ambiguity, dependency and the denial of social space, she reveals that mixed race is essentially a conditional state. The underlying ideology that defines each community is therefore subject to frequent transformation in the face of social, economic and political change." "As mixed race groups across the world call for the right of self-definition, this book reveals that it is through understanding the plurality of the category of mixed race that we are best able to transcend the idea of 'race' and challenge the racial axes of social division. The book includes an examination of the folklore around racism and anti-racism, and the agencies through which ideologies of race are propagated, including social welfare groups, religious groups, scientific texts, and the family."--Jacket.